SOSIALISASI PERATURAN DAERAH KOTA PALANGKA RAYA NOMOR 3 TAHUN 2022 TENTANG PENGURANGAN KANTONG PLASTIK PADA KOMUNITAS UMKM PELABUHAN RAMBANG KOTA PALANGKA RAYA - Sahay, Marvy Ferdian Agusta; Syamsuri, Syamsuri; Ulfah, Sri Mujiarti; Jaya, Imanuel; Ayu, Katriani Puspita; Angela, Vivi Friskila; Grestyana, Nadya; Selvia, Fitriana; Melio , Edward; Santoso, Yonathan Ari; Thareq, Subhan Ilham; Sintha, Melia; Christina, Meilianna Devita; Rasan, Febriomico Griando (Jurnal Abdimas Bina Bangsa, 2024)
The issue of increasing production costs, difficulty in obtaining plastic bag replacement materials, and the habit of SMEs in using plastic bags in packaging are one of the causes of the increasing volume of plastic waste in the Rambang Harbor area of Palangka Raya City. The community service was carried out by the Palangka Raya University community service team through the method of socializing the Regional Regulation of Palangka Raya City Number 3 of 2022 concerning reduction of plastic bags to SMEs at Rambang Harbor to reduce the growth of plastic waste. The results of the community service activities that have been carried out, providing replacement incentives for SMEs, and providing access to plastic bag replacement materials products, as well as innovative products are willingness for SMEs of Rambang Port to the government to reduce the use of plastic bags.